Strengthening Student Entrepreneurship Capacity through Business Legality, Digital Marketing, and Branding Strategy Training at Universitas Muhammadiyah Riau (ARSY : Jurnal Aplikasi Riset kepada Masyarakat, 2025)
The development of student entrepreneurship is an essential need for universities in preparing graduates who are productive, innovative, and competitive in the era of the Industrial Revolution 4.0. However, student entrepreneurs face various challenges, including limited managerial knowledge, human resources, and business legality, which often result in unsustainable ventures. This study aims to enhance the entrepreneurial capacity of students at Universitas Muhammadiyah Riau (UMRI) through entrepreneurship training and mentoring covering three main aspects: (1) business legality and licensing, (2) social media & content marketing, and (3) business development and branding strategies. The implementation method was carried out through participant selection, module preparation, simulation-based training, intensive mentoring, as well as monitoring and evaluation. A total of 20 students involved in 10 business ventures participated in this program. The results showed a significant improvement in students’ entrepreneurial capacity, as evidenced by the issuance of 10 business legality documents, 2 trademark proposals, and students’ ability to produce digital marketing content and business development and branding strategy documents. This training proved effective in strengthening students’ managerial capacity and business knowledge, as well as encouraging the sustainability of student businesses at UMRI. Thus, the program can serve as a campus-based entrepreneurship development model that addresses the limitations of students’ business knowledge and experience.Keywords: student entrepreneurship, business legality, digital marketing, branding, UMRI.
Keywords: kewirausahaan mahasiswa, legalitas usaha, pemasaran digital, branding, UMRI